The Essence of Humanity and the Philosophy of Islamic Education - Apriliyani, Subhiyah; Nuryaman, Handi; Arif Nurrahmat, Jafar; Sahrodi, Jamali; Iwan (International Journal on Higher Education Issues, 2025)
This abstract discusses the importance of understanding the essence of humanity within the context of Islamic education philosophy. Human existence, as both a subject and object of education, has long been a topic of exploration. Philosophical thinking is necessary to comprehend the nature of humanity, as it involves the complexities of character and knowledge. Islamic educational philosophy addresses the essential issues of education, providing a foundational, rational, and comprehensive perspective on the challenges faced in education. It explores the essence of human nature, emphasizing the need for an education system that aligns with Islamic values, based on the Qur'an and Hadith, and guided by the wisdom of Islamic scholars. Through this approach, Islamic educational philosophy offers solutions to educational problems, with a focus on developing a person who embodies Islamic teachings in both intellect and character